2018
DOI: 10.1121/1.5053586
|View full text |Cite
|
Sign up to set email alerts
|

Analytical coupled vibro-acoustic modeling of a cavity-backed duct-membrane system with uniform mean flow

Abstract: Sound propagation in a flow duct is a complex and technically challenging problem. The presence of flexible vibrating walls inside the duct creates additional difficulties to the problem due to the complex vibro-acoustic and aero-acoustic couplings involved in the system. An accurate prediction of the coupled system response is of great importance for a good understanding of the underlying physics as well as the optimal design of relevant noise suppression devices. In the present work, a unified energy formula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…Recent studies have shown that techniques such as resonant acoustic rheology based on interfacial capillary waves provide a new method to quantify the properties of membrane surface tension [ 62 ]. This approach allows non-contact measurements of the viscoelastic properties of biological samples, providing insights into phenomena such as tissue diffusion and cell sorting [ 63 ].…”
Section: Measurement Of Cell Membrane Surface Tensionmentioning
confidence: 99%
“…Recent studies have shown that techniques such as resonant acoustic rheology based on interfacial capillary waves provide a new method to quantify the properties of membrane surface tension [ 62 ]. This approach allows non-contact measurements of the viscoelastic properties of biological samples, providing insights into phenomena such as tissue diffusion and cell sorting [ 63 ].…”
Section: Measurement Of Cell Membrane Surface Tensionmentioning
confidence: 99%